The Role of CSR and ISO 14001 in Enhancing Environmental Performance: The Mediating Effect of Environmental Accounting - Ohorella, Rizki Wahyu Utami; Mokoginta, Rena Mustari (International Journal of Economics Development Research (IJEDR), 2024)
When a company seeks to implement ISO 14001, it is committed to continuously improving its environmental performance. International standard certification of the ISO 14001 Environmental Management System and carrying out social responsibility where CSR conceptualises the triple bottom where the purpose of establishing a business is not solely to seek profit (profit), but also to participate in the welfare of society (people), to ensure survival (planet) so that CSR is expected to affect investors' views on the value or success rate of the company. This study aims to determine the effect of CSR, ISO 14001, and Environmental Accounting on the environmental performance of mining companies. This research design uses an explanatory quantitative type.